Law and Human Genetics : Regulating a Revolution. - Brownsword, Roger (Hart Pub., 1998)
As developments in human genetics proceed apace, the regulation of genetic research and its applications is set to represent one of the major legal challenges of the next century. At every turn - in the fields of medicine and commerce, in insurance and employment, in the family and even in the criminal justice system - advances in human genetics threaten to transform our understanding of ourselves and the basis upon which we relate to one another. This special issue of the Modern Law Review addresses a range of key issues - conceptual, ethical, political and practical - arising from the regulat.